Fast Food - Edited by Stephen, Wendy (London Murdoch, 2006)
Fast food cooked in a variety of ways including pan, pot, wok, grill and oven - Fast sweet food
Include Colored Illustration, Indexes
Keywords: Quick and easy cooking